Calculation of Number of Residents by Floor Placement of Elderly Medical Welfare Facilities Using Pathfinder - Seo Young, Kim; Ha Sung Kong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this study, the number of residents by floor placement of the elderly medical welfare facility was calculated using Pathfinder program. The first scenario showed that adequate number of residents by floor placement is less than 25. The second scenario showed that showed that adequate number of residents by floor placement is less than 24. The third scenario showed that showed that adequate number of residents by floor placement is less than 27. The fourth scenario showed that showed that adequate number of residents by floor placement is less than 27. Overall, evacuation process is faster when staff are placed on the higher floor rather than first floor, and when male residents are placed on the lower floor than female residents. Henceforth, more research is needed to study the evacuation time in relation to fire extinguishing facility operation and to study the evacuation time when there is a visual field defect due to smoke and fire.